Programmed Emission Transformations: Negative‐to‐Positive Patterning Using the Decay‐to‐Recovery Behavior of Quantum Dots. Issue 1 (22nd September 2016) - Malak, Sidney T.; Smith, Marcus J.; Yoon, Young Jun; Lin, Chun Hao; Jung, Jaehan; Lin, Zhiqun; Tsukruk, Vladimir V.
Abstract : Positive and negative photoluminescent photopattern contrasts arising from intrinsic modification of quantum dot (QD) emission (decay or recovery) upon exposure to light are reported. The ability to fabricate a variety of photopattern types using a single type of quantum dot is due to a two‐step decay‐to‐recovery evolution upon light exposure. It is shown that high‐contrast photopatterns spanning mm 2 areas can be fabricated within seconds with a facile one‐step process, representing a drastic reduction in the time required to develop an emissive pattern in a QD‐polymer film (from hours to seconds). Furthermore, the controlled light exposure allows for a programmed transformation of the emissive pattern contrast, with a reversal of the bright/dark regions of the QD‐polymer photopattern demonstrated. Finally, it is shown that the photopatterns can be stored over a period of time and then "recharged" using simple light exposure to partially recover the intensity and contrast of aged photopatterns. The outlined patterning strategies open up new pathways for facile, one‐step parallel fabrication of anti‐counterfeiting emitting labels and light sensors, as well as for gain‐loss parity‐time systems where an emission contrast is required but where physical patterning may not be appropriate. Abstract : The unique decay‐to‐recovery behavior of quantum dot emission allows for the fabrication of a variety of photopattern types including negative and positive, as well as negative‐to‐positive contrast switching.